Pemberdayaan UMKM Lokal Melalui Sosialisasi, Pelatihan SEO, dan Google Maps Di Kelurahan Tanjungsari, Surabaya - Santoso, Marsha Natania; Arianto, Dita Charolina Evangelista Cahyani; Vebryna, Esha Nanda; Valencia, Aisa Renata; Chairil, Augustin Mustika (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy but continue to face major challenges in digitalization, particularly in optimizing online promotional media. Through the Community Service Program (KKN) In Tanjungsari Village, Sukomanunggal District, Surabaya City, a team of students from Universitas Pembangunan Nasional